Managing volunteer engagement in reference to empirical research - Janik, Tomasz; Beck-Krala, Ewa (Managerial Economics, 2019)
Engagement and volunteerism are important issues in the area of Human Resource Management. Organized in Krakow in 2016, World Youth Days (WYD) exposed many phenomena related to these areas, creating an interesting research fi eld. This paper identifi es and explains the terminology and concepts existing in the literature that concern engagement and characterizes the volunteering issue in the context of Polish social reality. The article also contains selected fi ndings of a survey conducted among World Youth Days volunteers. Based on it, this paper shows the characteristics of selected relationships and the social and demographic conditions of volunteerism in that specific research perspective. Research has shown that, within the volunteers’ groups, it is possible to use professional and modern management methods. Our fi ndings lead to a set of suggestions for team leaders that have the potential of creating a higher level of engagement among participants and may enable better organizational management.